A new ELISA for determination of potency in snake antivenoms - Rial, A. (2006)
Abstract A competitive ELISA for potency determination of bothropic equine antivenom was developed and compared to the conventional in vivo ED50 assay, with the aim of partially substituting the in vivo assay in the monitoring of antivenom immunoglobulin levels. On this purpose, blood samples were taken at different times during and after the immunization protocol of the lot of horses used for production of snake antivenom at the Instituto de Higiene, Uruguay. Both the competitive ELISA and the ED50 assay were performed on those samples. In addition, a group of five commercial pepsindigested antivenoms were tested by both methods. A significant (Po0.001) correlation (Pearson’s r ¼ 0.957) was found between the ELISA titres and the corresponding ED50 values, indicating that the in vitro test can estimate the neutralizing antibody capacity of the sera as well as the in vivo assay. By means of this new ELISA, it was found that the immunized animals maintained good venom antibody titres, in the order of 20–50% of the maximum achieved, even 10 month after the end of the immunization schedule. The main advantage of our ELISA design is its ability to correctly estimate the neutralization capacity of crude hyperimmune plasma and antivenom sera independently of their antibody composition in terms of whole IgG or F(ab0)2 fragment.in vivo ED50 assay, with the aim of partially substituting the in vivo assay in the monitoring of antivenom immunoglobulin levels. On this purpose, blood samples were taken at different times during and after the immunization protocol of the lot of horses used for production of snake antivenom at the Instituto de Higiene, Uruguay. Both the competitive ELISA and the ED50 assay were performed on those samples. In addition, a group of five commercial pepsindigested antivenoms were tested by both methods. A significant (Po0.001) correlation (Pearson’s r ¼ 0.957) was found between the ELISA titres and the corresponding ED50 values, indicating that the in vitro test can estimate the neutralizing antibody capacity of the sera as well as the in vivo assay. By means of this new ELISA, it was found that the immunized animals maintained good venom antibody titres, in the order of 20–50% of the maximum achieved, even 10 month after the end of the immunization schedule. The main advantage of our ELISA design is its ability to correctly estimate the neutralization capacity of crude hyperimmune plasma and antivenom sera independently of their antibody composition in terms of whole IgG or F(ab0)2 fragment.50 assay were performed on those samples. In addition, a group of five commercial pepsindigested antivenoms were tested by both methods. A significant (Po0.001) correlation (Pearson’s r ¼ 0.957) was found between the ELISA titres and the corresponding ED50 values, indicating that the in vitro test can estimate the neutralizing antibody capacity of the sera as well as the in vivo assay. By means of this new ELISA, it was found that the immunized animals maintained good venom antibody titres, in the order of 20–50% of the maximum achieved, even 10 month after the end of the immunization schedule. The main advantage of our ELISA design is its ability to correctly estimate the neutralization capacity of crude hyperimmune plasma and antivenom sera independently of their antibody composition in terms of whole IgG or F(ab0)2 fragment.Po0.001) correlation (Pearson’s r ¼ 0.957) was found between the ELISA titres and the corresponding ED50 values, indicating that the in vitro test can estimate the neutralizing antibody capacity of the sera as well as the in vivo assay. By means of this new ELISA, it was found that the immunized animals maintained good venom antibody titres, in the order of 20–50% of the maximum achieved, even 10 month after the end of the immunization schedule. The main advantage of our ELISA design is its ability to correctly estimate the neutralization capacity of crude hyperimmune plasma and antivenom sera independently of their antibody composition in terms of whole IgG or F(ab0)2 fragment.50 values, indicating that the in vitro test can estimate the neutralizing antibody capacity of the sera as well as the in vivo assay. By means of this new ELISA, it was found that the immunized animals maintained good venom antibody titres, in the order of 20–50% of the maximum achieved, even 10 month after the end of the immunization schedule. The main advantage of our ELISA design is its ability to correctly estimate the neutralization capacity of crude hyperimmune plasma and antivenom sera independently of their antibody composition in terms of whole IgG or F(ab0)2 fragment.in vivo assay. By means of this new ELISA, it was found that the immunized animals maintained good venom antibody titres, in the order of 20–50% of the maximum achieved, even 10 month after the end of the immunization schedule. The main advantage of our ELISA design is its ability to correctly estimate the neutralization capacity of crude hyperimmune plasma and antivenom sera independently of their antibody composition in terms of whole IgG or F(ab0)2 fragment.0)2 fragment.